A comparative analysis of the chemical composition of linear low density polyethylene polymers synthesised with 1- hexene comonomer under different catalytic conditions - Naidoo, Preloshni (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.